Introducing Commercial Finance into the Water Sector in Developing Countries - Bender, Kevin (World Bank, Washington, DC, 2017)
This guidance note provides an introduction to the role of commercial finance in the water and sanitation sector. Its aim is to help readers (development specialists) explore applications in their own countries. The note focuses primarily on commercial bank loans, and throughout the document the term commercial finance refers to commercial loans from domestic banks. However, much of the guidance could be applicable to debt capital market financing for water. While there is some research available on accessing international private finance for water infrastructure, the literature on facilitating local domestic finance (raised in local currency from local banks or lenders) is limited. This note aims to fill the gap and to present a process to readers who are not financial specialists and who may be unfamiliar with commercial banking. The target audience for this note is development specialists and local practitioners working in water and sanitation service delivery who want to explore the possibility of introducing access to commercial finance to service providers in their country. The note also provides guidance that may be helpful to other local stakeholders involved in or contemplating various phases of building a commercial finance market. Readers who are less familiar with lending and infrastructure finance may wish to start with the appendix B on commercial finance basics. The note takes a holistic sector approach to the introduction of commercial finance, targeting the three key stakeholders: borrowers, lenders, and government entities. This note covers a four-phase framework: (i) Phase I: Scoping the Market; (ii) Phase II: Designing and Building the Market; (iii) Phase III: Executing the Deal; and (iv) Phase IV: Monitoring and Evaluating Deal Success.